Enhancing Numeracy of Grade VIII Students SMPK Adisucipto Kupang via Augmented Reality-Embedded Ethnomathematical Learning - Samuel Igo Leton (CV. Samuel Manurung and Co, 2026)
This study developed Augmented Reality (AR)‑embedded ethnomathematical learning materials to enhance junior secondary students’ understanding of relations and functions. Using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluations), the development integrated Timorese cultural artefacts as conceptual contexts and AR visualizations as representational support. In collecting data, we used questionnaires, interviews, and learning outcome tests. Expert validation indicated a very high level of validity (mean 87.15), while student responses (81.2%) and teacher evaluations (36/40) confirmed the practicality and classroom suitability of the materials. Effectiveness testing demonstrated substantial improvement in conceptual understanding, as reflected in pretest–posttest gains and N‑Gain scores categorized as moderate to high. The findings show that the purposeful integration of cultural contexts and AR strengthens conceptual meaning‑making, increases learning engagement, and effectively bridges students’ cultural practices with formal mathematical representations